Hukum Islam dalam Ketatanegaraan Indonesia - Veronika Roselino; Muannif Ridwan (Jurnal Indragiri Penelitian Multidisiplin, 2022)
Islam came to Indonesia with complexity, namely not coming from one place, from the role of a group, nor at the same time. This phenomenon becomes interesting because we then see various theories about the emergence of Islam in Indonesia. However, the emergence and development of Islam in Indonesia is a subject of change. This of course does not stop the study and discussion of Islamic infiltration, because there is still a lot of scope to correct or strengthen existing theories. However, after entering the period of independence, starting with the reign of the Old Order, the New Order and up to the current Reformation Order, Islamic rule has increasingly accepted its position and role in Indonesian constitutional life. In the third period of this order, laws and regulations that contain Islam and Islamic forums are increasingly proliferating using fertile and strategic terms. This paper will describe that Islamic rules have an important position in guarding the Indonesian state administration, towards a new Indonesia. Considering its revelationistic and rationalistic character and combining idealism and realism, Islamic law is able to guarantee the demands of the dynamics of the Indonesian state administration.